Scurrula ferruginea (Jack) Danser: Therapeutic Applications and Future Opportunities - Safrida Safrida; Afwa Hayuningtyas (Journal of Nutrition Science, 2021)
Scurrula ferruginea (Jack) Danser from Loranthaceae is one such mistletoe that grow in tropical countries and has been used as therapeutic agent for curing of diseases, such as anticancer, antihypertensive, antiviral, antimicrobial, antiasthma, anti-hyperglycemic, and analgesic. Regardless of S. ferruginea various kinds of health benefits, their available data and literature review are still limited, especially in Indonesia. The scientific studies existence in this review can promote the potency development of S.ferruginea. We suggest critical future opportunities and research directions of S.ferruginea that could improve understanding toward evidence-based medicinal herbs.